2021
DOI: 10.1177/00048674211025608
|View full text |Cite
|
Sign up to set email alerts
|

How do lipids influence risk of violence, self-harm and suicidality in people with psychosis? A systematic review

Abstract: Objectives: Low cholesterol has been linked with violent and suicidal behaviour in people with schizophrenia. This association, if consistently present, may be a promising biological marker that could assist clinicians in decision making regarding risk and treatment. We conducted a systematic review to assess whether there is a reliable association between lipid profile (total cholesterol, high- and low-density lipoprotein cholesterol, and triglycerides) and aggression, self-harm or suicide in people with schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…As recently reviewed [ 17 ], there are inconsistent data on the role of gender in aggression in the psychiatric ward: some studies ( n = 12) confirmed male gender as a risk factor for aggression, others found no relation ( n = 22), and some studies ( n = 3) reported that female gender is a risk factor for aggression. Therefore, it is still unclear whether male or female gender is a risk factor for aggression [ 13 ]. Since these data are not uniform, in the present study, we included only the female gender in order to exclude the possible influence of gender on aggression.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As recently reviewed [ 17 ], there are inconsistent data on the role of gender in aggression in the psychiatric ward: some studies ( n = 12) confirmed male gender as a risk factor for aggression, others found no relation ( n = 22), and some studies ( n = 3) reported that female gender is a risk factor for aggression. Therefore, it is still unclear whether male or female gender is a risk factor for aggression [ 13 ]. Since these data are not uniform, in the present study, we included only the female gender in order to exclude the possible influence of gender on aggression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review [ 13 ] included 23 studies that evaluated the association between lipid levels and aggression, violence, or suicidal behavior. Suicidal behavior and plasma lipid levels were assessed in 20 studies, and some studies reported low cholesterol levels in suicidal subjects, while others did not confirm these results.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations